The Role of Social Interaction in Shaping Tolerance Character Among Elementary School Students: Insights from Indonesia - Irma Irayanti; Muh. Ikhsan (Yayasan Zia Salsabila, 2025)
This study examines the role of social interaction in fostering tolerance among elementary school students in Indonesia. Grounded in social constructivist theory, it explores how collaborative and interactive experiences within schools shape students' character, particularly their ability to accept and respect differences. Employing a quantitative explanatory survey design, data were collected from 1,209 students in grades 4 to 6 across elementary schools and madrasah ibtidaiyah nationwide using structured questionnaires. Linear regression analysis assessed the relationship between social interaction (independent variable) and tolerance (dependent variable). The findings indicate a significant positive relationship, with a correlation coefficient (R) of 0.330 and a coefficient of determination (R²) of 0.109. This suggests that social interaction accounts for 10.9% of the variance in tolerance, while the remaining 89.1% is influenced by factors such as family environment, cultural values, and educational approaches. The regression model Y = 27.225 + 0.597X indicates that a one-unit increase in social interaction results in a 0.597-unit increase in tolerance. Although social interaction’s contribution is modest, the study highlights its essential role in fostering tolerance through peer interactions, group activities, and collaborative learning. These findings emphasize the need to integrate social interaction into school programs to promote inclusivity and empathy.